ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM MELANJUTKAN PENDIDIKAN PROFESI NERS DI STIKES HARAPAN BANGSA PURWOKERTO - Rahmaya Nova Handayani; Adiratna Sekarsiwi (Universitas Harapan Bangsa Purwokerto, 2015)
Based on the decree number 129 / U / 1998 makes Undergraduate nursing educationprograms implementing the educational curriculum of the nursing profession in the two (2 )phases , namely the phase of academic and professional stage which is a unity . Many people whocan not distinguish between SKp . and S.Kep , so some institutions recruit S.Kep . as aprofessional nurse when they do not have the ability as a nurse because not follow professionaleducation ( Ns . ) . As a result of the many graduates who did not take part in education until thestage of the profession . Study Program held STIKES Harapan Bangsa Purwokerto one of them isa professional course of study nurses Long-term goals determine the factors that influence whether or not a student interestsand continuing professional education nurses in STIKES Harapan Bangsa Purwokerto The research design is descriptive analytic cross - sectional approach . Unstratifiedsampling using random sampling with a sample size of 50 respondents . Respondents in questionare students who are studying nursing and professional nurses S1 . The research instrument aquestionnaire about the respondents' knowledge , perception , motivation and supprot system. Keywords : Interest , knowledge , perception , motivation , support system , nurses